2019
DOI: 10.4103/jfmpc.jfmpc_520_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and uptake of human papillomavirus vaccination among female undergraduates in Lagos State, Nigeria

Abstract: Background and Aims:Human papillomavirus (HPV) is a known cause of cervical cancer which is the second-most common cancer among women worldwide. HPV vaccination is a primary prevention to reduce the occurrence of cervical cancer. This study assessed knowledge, attitude and uptake of HPV vaccine among female undergraduates in Lagos State Polytechnic (LASPOTECH).Methods:A descriptive cross-sectional survey was conducted among 400 female undergraduates of LASPOTECH in August 2018. Participants were selected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 24 publications
6
25
5
Order By: Relevance
“…[ 22 ] Other barriers to HPV vaccine acceptance in the present study include concerns about side effects and fear of injections. [ 17 20 22 23 24 32 ] Additionally, health professionals were considered the most reliable sources of knowledge and awareness about HPV-related disease and vaccination; this finding is in agreement with those of other studies. [ 16 29 33 ] However, studies have shown that the internet, mass media, and social media were the most important sources of information on HPV-related problems and cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…[ 22 ] Other barriers to HPV vaccine acceptance in the present study include concerns about side effects and fear of injections. [ 17 20 22 23 24 32 ] Additionally, health professionals were considered the most reliable sources of knowledge and awareness about HPV-related disease and vaccination; this finding is in agreement with those of other studies. [ 16 29 33 ] However, studies have shown that the internet, mass media, and social media were the most important sources of information on HPV-related problems and cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
“…According to the study protocol, 84.8% of the participants showed poor total knowledge scores, similar to the findings of several studies in both developed and developing countries. [ 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] Thus, increasing the level of knowledge of cervical cancer in Saudi Arabia is important for the promotion of healthy behaviors and the use of preventive methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies carried out among female students in secondary schools and universities in Nigeria have alluded to this fact. [11][12][13][14][15] In a similar way, parents and caregivers of young people have demonstrated poor knowledge of cervical cancer prevention and screening for their children in Nigeria. 16,17 The deficiency of such knowledge may adversely affect the acceptability and uptake of HPV vaccine.…”
Section: Introductionmentioning
confidence: 99%